Mitigating poor environmental quality with technology, renewable and entrepreneur policies: A symmetric and asymmetric approaches - Udemba, Edmund Ntom; Emir, Firat; Philip, Lucy Davou (Pergamon-Elsevier Science Ltd, 2022)
This is dual analysis of Turkish sustainable development amidst some high industrial and economic activities. Turkey is currently prioritizing the economic growth to the environmental sustainability and trying to achieve its 2023 goals and place in top 10 economies by date. This action might spark increase in emission level and decrease the environmental quality for both term. For effective and clear analysis, we apply the empirical analyses with both symmetric (dynamic ordinary least square-DOLS) and asymmetric (nonlinear autoregressive distributed lag-NARDL) approaches in short run and the long run periods for policy inferences through forecast. We apply the economic features (entrepreneurs, FDI, technological innovation proxy by R&D, renewable energy and economic growth) of Turkey that are important in determining both economic and environment development of the country to investigate its ability to achieve its climate goals. Turkey's data of 1985-2018 were adopted. Findings from both approaches (symmetric and asymmetric) show that carbon emission can be reduced and good environmental quality obtained through the instruments of renewable energy, technological innovation, FDI and entrepreneurial activities. A nexus is established among the instruments (renewable energy, technological innovation, entrepreneur activities and FDI) pointing towards carbon mitigation for Turkey, and this gives support to the findings from both symmetric and asymmetric approaches. Also, from symmetric analysis with dynamic ordinary least square, EKC is found for the case of Turkey which shows the ability of Turkey achieving its climate goal if right policies are implemented. (C) 2022 Elsevier Ltd. All rights reserved.
Keywords: Energy policy: technological innovation; Entrepreneur activities; FDI; Turkish sustainability development; NARDL